Water footprint of the diet of adolescents in Brazil: relationships with fast food consumption and place of residence (Research, Society and Development, 2021)
The aim of this study was to estimate the water footprints of the diet of teenage schoolchildren in Brazil and the associations with territorial context and food routine. This is an ecological study based on microdata from sample 1 of the 2015 National Adolescent Health Survey, with which the average water footprint (WF) of adolescents' nutrition was estimated by category of analysis: Brazilian federation unit, geographic macro-region and by number of days a week attended fast food restaurants. Descriptive and spatial statistics were used to understand the distribution of these means in territorial analysis units and frequency in fast food. In Brazil, the average WF of the adolescents' diet was 2925.9 liters/kg. The distribution of WF showed a strong spatial correlation (Moran Local Index=0.773), with emphasis on the formation of the high-high cluster (Rio Grande do Sul, Santa Catarina, Paraná, São Paulo, Rio de Janeiro, Espírito Santo, Minas Gerais and Mato Grosso do Sul). In addition, the mean WF of this group's diet increased proportionally to the increase in the number of days that the adolescent used to eat at fast food. A direct relationship can be seen between the greater environmental impact of eating adolescents, more urbanized living areas and greater attendance at fast food restaurants. Assessing these associations is important for compressing public health and nutrition issues from the perspective of sustainability. Thus, strategies can be developed to reduce the environmental impact and improve the diet of this age group.